PENGOLAHAN SAMPAH SAYURAN MENJADI KOMPOS DENGAN METODE TAKAKURA - Larasati, Adella Atika; Puspikawati, Septa Indra (Jurnal Ilmu Kesehatan Masyarakat, 2019)
The increasing household activity is increasing also the amount of vegetables waste produced will cause a pile of decomposed waste, so that proper waste management is needed. The processing of waste done by the Community is still conventional that takes a long time so needed an innovation by re-utilizing garbage into compost with the method Takakura. This research aims to determine the comparison of physical parameters (temperature, pH, humidity, smell, color and texture) between the control group and the treatment group in making compost with Takakura method. This research method utilizes an experimental semi-quasi design with a control group and a treatment group conducted in the Environmental Health Laboratory of PSDKU Airlangga University in Banyuwangi during February-April 2019. The results showed that the parameters of physical quality compost vegetable waste without the addition of bioaktivator is the temperature of 29oC, pH 6.8, humidity 45%, colored blackish, smelling soil and texture like soil. While the parameters of physical quality compost vegetable garbage with the addition of Bioaktivator EM4 is 30oC temperature, pH 6.8, humidity 50%, colored blackish, smelling soil and texture like soil. Conclusion of making compost with vegetable garbage method Takakura obtained the temperature parameter of the treatment group higher than the control group, the pH of both groups, the humidity of the treatment group is higher or moist than With the control group as well as the color, smell and texture of both groups in accordance with the guidelines SNI 19-7030-2004. Keywords: compost, EM4, vegetable waste, takakura